Analisa Status Mutu Air Pada Musim Kemarau Berdasarkan Metode Indeks Pencemaran Di Tukad Yeh Poh, Kabupaten Badung - Diah Valentina Lestari; Andhita Triwahyuni (Program Studi Teknik Lingkungan Unmas Denpasar, 2021)
Tukad Yeh Poh is categorized as a sub-river basin unit which plays an important role for the irrigation purposes and daily life support for the surrounding areas. The water quality along the river is analyzed using Pollution Index (PI) method to compare nine parameters with the standard value class II, including seven chemical parameters (DO, COD, BOD, Pb, PO4, NO2, NO3, oil and fat) and microbiological parameter (Coliform) throughout three sampling points to represent the upstream, downstream and middle point. The measurement is following the administration area of Badung Regency during the dry season that is represented by June 2019. There are five chemical parameters showing a larger concentration compared to the standard value. Moreover, the PI calculation suggested that the upstream and middle point should be categorized as lightly polluted, while the downstream region labelled as moderately polluted.